Group Action Factor of Nail Fastener on the Wood Connection With Plywood Sides Plate - Tjondro, Johannes Adhijoso; Rosiman, Evan Kurnia (Jurnal Teknik Sipil, 2011)
Abstract. The group action factor was observed in this experimental study. The 18 mm thickness of plywood was used as sideâs plate and the main members were made from meranti (shorea sp.) and sengon (paraserianthes falcataria) species. The correlations of group action factor with a number of nails in a row was investigated under uni-axial compression loading test with one to ten nails variation in a row. The member connections with multiple 3 rows with 3, 6, and 9 nails in each row were also tested both under uni-axial compression and tension loading. The group action factor correlated to the number of nails for single row was obtained using the regression analysis. The regression equations presented was group action factor at the proportional limit (Cgp), group action factor at the 5% offset diameter (Cg5%), and group action factor at the ultimate load (Cgu). The connection strength at 5% offset diameter and proportional limit was closed to the strength design based on the draft of Indonesian Timber Code 2000. The ultimate strength is extremely higher than the design value, giving a sufficient safety factor. Based on this result, a simplified group action factor equation for connection with plywood sideâs plate was proposed.Abstrak. Faktor aksi kelompok diteliti dalam studi eksperimental ini. Plywood dengan tebal 18 mm digunakan sebagai pelat penyambung sisi dan kayu utama terbuat dari meranti (shorea sp.) dan sengon (paraserianthes falcataria). Korelasi antara faktor aksi kelompok dengan jumlah paku dalam satu baris diteliti dari pengujian dengan beban tekan uni-aksial dengan variasi satu sampai dengan sepuluh buah paku. Sambungan dengan 3 baris majemuk dengan 3, 6, dan 9 paku dalam satu baris juga diuji dengan uji beban tekan dan tarik uni-aksial. Faktor aksi kelompok yang dikorelasikan dengan jumlah paku untuk satu baris didapat dari analisa regresi. Persamaanpersamaan regresi yang disajikan adalah faktor aksi kelompok pada batas proporsional (Cgp), faktor aksi kelompok pada 5% offset diameter (Cg5%) dan faktor aksi kelompok pada batas ultimit (Cgu). Kekuatan sambungan pada 5% offset diameter mendekati kekuatan sambungan dari harga disain berdasarkan draft Peraturan Kayu Indonesia 2000. Kekuatan ultimit sambungan jauh lebih tinggi dari harga disain, memberikan faktor keamanan yang memadai. Berdasarkan hasil kajian ini, suatu persamaan sederhana untuk perhitungan faktor aksi kelompok dengan pelat penyambung sisi plywood disarankan.